Artificial Intelligence-A Key Note Biomarker in Drug Discovery and Development Running Title: ARTIFICIAL INTELLIGENCE - Madhavi Nimmathota; Merlin T Babu; S Tanusri; N Aishwarya; Rama Rao T (International Journal of Formal Sciences: Current and Future Research Trends, 2023)
The application of artificial intelligence (AI) has recently accelerated in several societal domains, with the pharmaceutical sector leading the way. This paper highlights the useful applications of AI in the pharmaceutical industry, including medication discovery and development, drug repurposing, and pharmaceutical quality improvement. Among others, productivity, clinical trials, etc., have reduced the workload of people and expedited the completion of goals. Crosstalk about the methods and instruments used to enforce AI, ongoing problems, and solutions to them is also explored, as is the role of AI in terms of efficiency, accuracy, and speed. AI has the potential to revolutionize the drug discovery process. However, the availability of high-quality data, addressing ethical issues, and using AI effectively all depend on an understanding of the limitations of AI-based techniques. This article discusses the advantages of AI in this field, along with potential solutions. The suggested barriers to the situation are the addition of data, comprehensible AI, and the incorporation of the potential benefits of AI in the pharmaceutical industry, as well as how it compares to conventional experimental methods. This paper underlines the potential of artificial intelligence in drug discovery and gives details about the possibilities for attaining.